Technologies Reshaping Warfare: Artificial Intelligence And U.S. Military Doctrine - Khassanay, A.M.; Baissalova, G.T.; Beissenbayeva, M.T. (Кұқық және мемлекет, № 1 (106), Maqsut Narikbayev University, 2025)
This study undertakes an analysis of the legal and ethical dimensions surrounding the utilization of artificial intelligence (AI) in military technologies, with a specific focus on autonomous weapon systems. Given the accelerating pace of AI development and its concomitant integration into the defense sector, the formulation of international legal norms governing the deployment of these technologies has become a matter of paramount importance. Particular attention is directed towards the existing discrepancies in the conceptualization of autonomous weapon systems between the United States and other international actors, including the People’s Republic of China. This analysis identifies key challenges pertaining to the legal regulation of autonomous weapons, their compatibility with established principles of international humanitarian law (IHL), and the multifaceted issues arising from the integration of AI into contemporary military operations. Furthermore, this study examines various U.S. initiatives and declaratory pronounce- ments aimed at establishing standards for the safe and ethical application of artificial intelligence within the military sphere. 1 Finally, emphasis is placed upon the exigency of continued global dialogue and enhanced interstate cooperation to ensure the preservation of international security and the mitigation of potential threats to global stability
Keywords: United States, military doctrines, international humanitarian law (IHL), artificial intelligence (AI), autonomous weapon systems (AWS)